American security strategy towards terrorism after September 11 attacks - Wael Zakaria Farag (Review of Economics and Political Science (REPS), 2020)
Purpose The purpose of this paper is to examine evolution of the American strategy toward terrorism in the aftermath of the events of September 11, 2001. In other words, this study revolves around a key question: How and why the American security strategy toward terrorism evolved in the aftermath of the September 11 attacks in 2001? Based on the neorealist approach in international relations, this paper attempted to answer that question: first, through defining the concept of terrorism and how the Americans perceive it; second, via pinpointing the characteristic of the American counter-terrorism strategy before September 11 attacks; and third, through examining the effects of those terrorist attacks on that strategy. Design/methodology/approach The nature of the subject of this study calls for reliance on the analytical descriptive approach to highlight the role and strategy of the USA in the fight against terrorism following the events of September 11, in addition to the use of the system analysis methodology, which can identify the inputs and outputs of the system that had an impact in formulating the US counter-terrorism strategy. Findings This study has come up with seven findings. The first finding was that the 9/11 attacks served as a turning point of the US counter-terrorism strategy and restructured its agenda. Confronting the communist threat had been its primary objective, until terrorism came to the fore and became its first and foremost priority. The USA vowed that terrorism is its enemy and waged the war on terror to thwart its risk as a global threat. The second finding revolves around the idea of double standards in the American foreign policy. True to its long-standing tradition of favoring its own interests, in complete disregard of the interests of any other party, the USA continued to uphold the double-standards policy. Originality/value This study adds a new study to the Arab Library in the field of counter-terrorism studies, national security strategies and American foreign policy. In addition, the researcher seeks to complete the scientific effort to study the US strategy against terrorism, with a clear impact on the development of the situation in the region. This study contributes to the study of how one of the great powers in the international system, the USA, deals with the terrorist organizations that have become widespread in the Arab region.
Keywords: 330; 11th; Anti-terrorism; September